Flood mitigation in Metro Manila - Liongson, Leonardo Q. (Philippine Engineering Journal)
Tropical Storm Ondoy (Ketsana) crossed Metro Manila and the adjacent river basins in a later wet-season episode of 2009, starting in the evening of September 25, 2009 and continuing into the next day of September 26, 2009. TS Ondoy brought very intense and heavy rainfall to the region: meaning that record amounts of rains fell over a very short time period of 12 hours to 24 hours, which are estimated to occur at an average annual frequency of 1 in 100 years or even higher, depending on the measuring location in the region. The rains generated record-magnitude flood flows and inundation in the Pasig-Marikina River Basin in Metro Manila, and the Laguna de Bay region. This article briefly explains the present situation in the flood management in Metro Manila, covers the various government flood-mitigation projects, and after briefly describing the pattern and statistics of the rainfall and flood flows associated with the major storm and their resulting physical impacts, risks and damages to the metropolis, provides recommendations, both in terms of structural and non-structural mitigation measures, for everyone concerned.